Optimization and Vibration Response Analysis of Vehicle Suspension Structure With Inerter - Haiqing Lu; Fanjie Li; Xiaopeng Li; Haozhe Wang (Shock and Vibration)
The structural composition and component parameters of the suspension will have an impact on the vibration reduction and handling performance of the vehicle. This paper innovatively proposes a suspension structure using an inerter and mathematically models it. To further improve the comprehensive performance of the designed suspension, the component parameters are optimized and the bushing is selected based on merit. The influence of parameters on suspension response is obtained using numerical methods, and the damping effect and handling performance of the suspension are deeply studied. Based on the analysis results of this paper, the designed suspension structure and its optimized design have effectively improved the overall performance of the vehicle. In addition to optimizing the parameters of suspension components, optimizing the selection of suspension bushings also has a positive impact on the overall performance of the vehicle. Therefore, this study provides a new design approach for improving the overall performance of suspension systems.